Challenges of Plastic Waste and It’s Recycling, A Threat to Environment: A Case Study of Kanpur City - Dr. Arti Vishnoi; Akasnsha Dwivedi, (Indian Journal of Social Science and Literature (IJSSL), 2024)
Materials and manufactured products process which fluctuate the balance of their production and rate of destruction are usually led to retrogression in the environment. Plastic products are considered one such material which gives rise to a big threat towards environment. A huge-huge amount of plastic in many forms is produced and dropped into the environment and naturally the homeostatic process of environment is itself unable to degrade the material produced with that’s why plastic recycling is an important issue in present scenario of the society. Un-organized recycling and non-biodegradability of plastic products produce the degree of devastation to the environment and the consequences of devastation are directly proportional to the health and life expectancy of mankind. This paper tries to deal with the investigation about the challenges of plastic waste as well as plastic bags that turns into a threat to the environment. Mostly, plastic waste is considered recyclable, but with the passing of time it is noticed that recycled products are proved more harmful to the environment so it is crystal clear that recycling is not more sheltered and permanent solution for the plastic waste disposal.